Pemodelan Interaksi Turunan Potensial Asam Benzoilsalisilat dengan Reseptor Enzim Siklooksigenase-2 - Natalia, Ongki; Caroline, Catherine; Soekardjo, Bambang (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2013)
The research of synthesize and quantitative structure activity relationship of benzoyl salicylic acid derivatives for analgesic activity in mice had been done by Soekardjo et al. (2009). From the fourteen compounds that had been synthesized, it has been known that O-(3-chlorometilbenzoyl) salicylic acid had the best analgesic activity (EDso value was 15.7396 mg/kg) while the EDso value of acetyl salicylic acid was 3296 mg/kg. Therefore further studies were carried out to determine the interaction modelling of potential benzoy/saJicyJic acid derivatives with enzyme cyclooxygenase-2 receptor by using Glide (Schrodinger license). The result showed that the GScore of 0-(2-trifluoromethoxybenzoyl)salicylic acid: -9.97, 0-(2.4-dimethylbenzoyl)salicylic acid: -9.94, O-(2-fluorobenzoyl)saJicylic acid : -9.62 and 0-(2.3-dimethy/chlorobenzoyl)salicylic acid : -9.49 more active than O-(3-chloromethylbenzoyl)saJicylic acid (-9.48), which GScore of each compound less than 0-(3-chloromethylbenzoyl)salicylic acid that had been synthesized. 0-(2-trifluoromethoxybenzoyl)salicylic acid, 0-(2.4-dimethylbenzoyl)salicylic acid, O-(2-fluorobenzoyl) salicylic acid and O-(2.3-dimethylchlorobenzoyl) salicylic acid are compounds that have a good potency as an analgesic. Interaction of potential benzoy/salicy/lc acid derivatives with enzyme cyclooxygenase-2 receptor was on residues Tyrosine 385, Leusine 531, Tyrosine 355 dan Arginine 120.